Implementing mass transit: a case study of the CyRide system in Ames, Iowa and its implications for mass transit in Manhattan, Kansas - Zevenbergen, Philip G. (Kansas State University, 2010)
The purpose of this document is to use an existing transit system as the standard by which another community can model their own. It begins with the discussion of a brief history of mass transit in the United States—focusing on the detail that competing automobile manufacturers began the demise of transit ridership in this nation. As the 1950s came to a close, the nation’s transit systems saw the peak of ridership. However, the post-war era brought about massive suburbanization and more automobiles per household. The American no longer needed to ride transit, except for those still living in the dense urban cores of cities like New York City. The document moves into the discussion of the fundamentals of mass transit. It explains the importance of population base, ridership, and funding. Depending on the type of system, a minimum population base is recommended in order to support the proper system. Ridership is a key focus of transit, for without it, a community is just wasting resources. Finally, funding is very important. No transit system can support itself on fares alone and still remain a viable alternative to the automobile. Transit systems must procure funding from a variety of sources including all levels of government in order to obtain sufficient revenue to operate successfully. The heart of the document focuses on the CyRide bus system in Ames, Iowa—serving the Ames community and Iowa State University since 1976. CyRide is a special system in that it serves a total population of only 54,000, but sees an annual ridership of 5 million. Their success is based on a longstanding relationship with the community complimented by staff that posses the passion to ensure the highest quality service day-in and day-out. This report discusses the fine details of how that system functions on all levels. The document concludes with the discussion of Manhattan, Kansas—a city with approximately the same population as Ames, and is home to Kansas State University, which as approximately the same student enrollment as Iowa State. Manhattan currently does not have a transit system, but is seeking to implement one in the coming years. The overall intent of this report is to draw conclusions based on the performance of CyRide and provide recommendations to the City of Manhattan regarding the implementation and operation of a transit system.
Keywords: Transportation planning; Mass transit; Bus system; CyRide; College towns; Manhattan Kansas; Transportation (0709); Urban and Regional Planning (0999)